Implementasi Media Clay Sebagai Stimulasi Perkembangan Motorik Halus Anak Usia Dini - Sulalah, Anis; Farida, Siti; Walidah, Zianatul (Generasi Emas : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Fine motor skills in early childhood require stimulation through activities that suit their characteristics. However, in the field, children are still found to have difficulty coordinating finger movements and limited use of manipulative media. This study aims to describe the process of stimulating fine motor skills in children aged 4-5 years through clay play activities in Group A of RA Asy-Syuhada'. The study used a descriptive qualitative approach with 9 children as purposively selected subjects. Data were collected through observation and interviews. The results showed that clay play activities can stimulate children's fine motor skills through squeezing, pressing, rolling, and shaping activities. These activities train the strength of small muscles in the hands, improve eye-hand coordination, and flexibility of children's fingers. Thus, playing with clay is proven to be effective as a medium for stimulating fine motor skills in early childhood.